ANALISIS KESANTUNAN BERBAHASA POLITIKUS DALAM PROGRAM INDONESIA LAWYERS CLUB DI TV ONE - Rani Noeraeni (CV. ADIBA AISHA AMIRA, 2023)
The background of this research is because the increasing of the case related to the violation on ITE law which done by society or even by prominent figure. This caused by inability of a person to manage his word in spoken or written form. This condition describes the reduction of politeness in speaking. The objectives of this research are to give a description about the realization of the principle of the prominent figure’s speech based on the theory of Leech, to describes the realization of the function of the prominent figure’s speech based on the theory of Charlie, to describes the politeness degree of the good manner in speech of prominent figure, and to describes the lesson material of discussion text produced from this research. The source of data taken on this scientific research is the program of “Indonesia Lawyer Club”. The data of this research is the speech of the prominent figure or the resource person in form of sentences or words. This research uses the descriptive method and the technique of documentation. The result of this research is describing the politeness degree of the prominent figure belonging to the category best politeness. While the one prominent figure just belonging to the politeness category. Those prominent figures have reflected the value of politeness which is realized by the comprehension of wisdom norm, generosity norm, appreciation norm, modesty norm, conciliation norm and sympathy norm. From the six norms above, the wisdom norm is not only the one that be obeyed but also the one that be broken. The function of statement discourse is the one that stated much by the prominent figure. While, the function of apologize discourse is the one that stated less. The result of this research used as a module about discussion text that can be applied in Junior High School.